Cultural Capital of Minangkabau Nomads in the 2019 Legislative Election in Indonesia - Hidayat, Novendra; Darmawan, Budi; Rahmad Putra, Gennta (Indonesian Association for Public Administration (IAPA), 2023)
This study examined the cultural capital possessed by Minangkabau nomads as the candidates of the DPR-RI Legislature in the 2019 Legislative Elections. Minangkabau is one of the ethnic groups in Indonesia which maintains a matrilineal kinship system and a tradition of merantau (travelling in pursuit of success). Merantau becomes a significant investment used by Minangkabau nomads to gain vote support for their candidacy as a member of the DPR-RI legislature in electoral political contestation, including the 2019 Legislative Election. The study utilized a qualitative descriptive method to collect data through interviews and documentation studies. The study results revealed that the figure of Minangkabau nomads candidates possessed the cultural capital and were able to manage this cultural capital to succeed in gaining significant victories in their respective constituency. The cultural capital of Minangkabau nomads could be seen from the two figures of Minangkabau nomads legislative candidates, namely Fadli Zon and Jon Erizal, including the institutionalized tradition of merantau, and the role Tungku Tigo Sajarangan (the traditional leaders) in the matrilineal kinship system. Through adequate cultural capital, the Minangkabau nomads were able to secure a big victory in their respective electoral districts.